The Influence of Behavioristic Counseling on Students' Toxic Relationships - Jaya, Ari Safaryan; Hariadi, Ahmad; Sulastri, Ni Made; Zuhairani, Siti (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2024)
The objective of this study was to evaluate the influence of behavioristic counseling on students' toxic relationships. A quantitative research design with a One Group Pre-test Post-test approach was employed to measure the effect of the counseling intervention on eighth-grade students at SMPN 4 Mataram. The population consisted of 378 students, with a sample of 96 selected based on high levels of toxic relationship behaviors. Data collection involved a validated questionnaire, observations, interviews, and documentation reviews. The intervention included three sessions of behavioristic counseling focusing on modeling techniques. Data analysis was performed using a t-test to compare pre-test and post-test scores. Results indicated significant improvements in students' behaviors post-intervention, with a majority showing reduced levels of toxic relationship behaviors. The t-test analysis confirmed the intervention's effectiveness, with a t-value of 7.459, surpassing the critical value of 2.262. The study recommends implementing behavioristic counseling in schools to address toxic relationships, emphasizing the need for personalized approaches to cater to individual student needs. These findings highlight the potential of behavioral counseling to improve students' social interactions and overall well-being, suggesting further research to refine and expand this intervention method.